A DESCRIPTIVE ANALYSIS OF ARABIC SENTENCE STRUCTURES IN @BRAYFAQOT TIKTOK CONTENT - I Isabella; Nabilah Faradiba; Rizkyana Wahyu Laras Pertiwi (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study investigates the use of Arabic syntactic structures in educational content on the TikTok account @Brayfaqot through a descriptive qualitative approach. The research aims to identify how Arabic sentence patterns are adapted and presented in digital short-form media. Data were collected from selected TikTok videos using non-participatory observation and documentation, then analyzed based on Arabic syntax theory. The findings reveal that the content employs various sentence types such as istifhām (interrogative), amr (imperative), nahy (prohibitive), and khabariyyah (declarative) forms, commonly structured as jumlah ismiyyah and jumlah fi‘liyyah. These structures are integrated with visual and interactive elements that enhance comprehension in digital learning contexts. This research contributes to the emerging field of digital Arabic linguistics by providing empirical insights into how syntactic features function within social media–based Arabic education.